Cognitive Health Worries, Reduced Physical Activity and Fewer Social Interactions Negatively Impact Psychological Wellbeing in Older Adults During the COVID-19 Pandemic - Sutton, Emma; Catling, Jonathan; Segaert, Katrien; Veldhuijzen van Zanten, Jet (Frontiers in Psychology, 2022)
The Coronavirus pandemic has significantly affected psychological wellbeing in older adults, with cases of depression, anxiety and loneliness rising in the general population. Cognitive health has also potentially been affected, as social isolation can lead to cognitive decline. Worrying about cognitive health can be damaging to psychological wellbeing and is especially relevant to explore in the context of the Coronavirus pandemic. The objective of the present study was to explore the associations between cognitive health worries and wellbeing, and to investigate whether physical activity and social contact can mitigate negative effects of the pandemic on psychological wellbeing. Older adults (N=191) completed an online survey which included measures of cognitive health worries, depression, anxiety, loneliness, social isolation, fatigue, impact of the Coronavirus pandemic, quality of life, subjective vitality, and physical activity. Analyses indicated that cognitive health worries, lower levels of physical activity and smaller amounts of social interaction were associated with poorer psychological and physical wellbeing. Results showed that worrying about cognitive health is associated with poorer wellbeing, and so interventions are needed to encourage positive cognitive functioning in times of social isolation. Promoting physical activity and social interaction is also beneficial, as results show that exercise and social contact are linked with improved wellbeing.